2017
DOI: 10.4034/pboci.2017.171.19
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Cross-cultural Adaptation of the Oral Health Literacy Assessment-Spanish to Brazilian Portuguese

Abstract: Objective: To translate the Spanish version of the instrument to measure oral health literacy-Oral Health Literacy Assessment-Spanish (OHLA-S)-into Portuguese (Brazilian) and perform their cross-cultural adaptation. Material and Methods: OHLA-S evaluates the level of oral health literacy from questions measuring pronunciation and comprehension skills of 30 dental terms concerning the etiology, anatomy, prevention and treatment of oral conditions. A committee of experts was created to evaluate all the steps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…A detailed description of the measurement tools is shown in Table 2. [28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], and only one study had examined the "decision-making" dimension [40]. Dimensions of evaluation, responsibility and interaction had not been measured in any instrument ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the measurement tools is shown in Table 2. [28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], and only one study had examined the "decision-making" dimension [40]. Dimensions of evaluation, responsibility and interaction had not been measured in any instrument ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results of methodological quality evaluation of the tools showed that, out of the 21 tools examined, 9 tools at least in one dimension were in the category of poor, which indicated the poor quality of that area [29-31, 33-37, 39, 45].The results of tool review using the COSMIN checklist showed that, 19 studies at least in one dimension had a "fair" quality, which indicated the suspected methodological quality [28,29,[31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48]. Also, 20 and 4 articles at least in one dimension had a "good" [28,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and "excellent" [33,35,43,44] quality, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also a summary of the quality of the domains examined on the basis of a checklist COSMIN for oral health assessment tools reported in the Supplementary material 3. The results of methodological quality evaluation of the tools showed that, out of the 21 tools examined, 9 tools at least in one dimension were in the category of poor, which indicated the poor quality of that area [33-35, 37-41, 43, 49].The results of tool review using the COSMIN checklist showed that, 19 studies at least in one dimension had a "fair" quality, which indicated the suspected methodological quality [32,33,[35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52]. Also, 20 and 4 articles at least in one dimension had a "good" [32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and "excellent" [37,39,47,…”
Section: Resultsmentioning
confidence: 99%
“…Four tools, by examining seven domains, had paid the most attention to the domains in the psychometric section [39,45,[47][48][49], and the two tools of ToFHLiD and OHLA-B had evaluated the minimum domains in the COSMIN checklist [33,50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation